Direct observation of the nutrition care practices of Australian general practitioners - Ball LE; Desbrow B; Yelland M; Leveritt MD (CSIRO Publishing, 2014)
INTRODUCTION: Nutrition care refers to nutrition-related advice or counselling provided by health professionals in an attempt to improve the nutrition behaviour of patients. AIM: The aim of this study was to describe the practices of a sample of Australian general practitioners (GPs) when providing nutrition care to adult patients. METHODS: Eighteen GPs (13 male, 5 female) were observed by fourth-year medical students during their general practice rotation. Each GP was observed for five consultations that included nutrition care, totalling 90 observed consultations. In each consultation, students completed a 31-item nutrition care checklist of nutrition care practices that could feasibly occur in a standard consultation. Each practice was marked with either a 'yes' (completed), 'no' (did not complete) or 'completed by practice nurse prior to or after the consultation'. RESULTS: Twenty-eight nutrition care practices were observed at least once. The most frequently observed practices were measuring and discussing blood pressure (76.7%; n=69), followed by general questions about current diet (74.4%; n=67). Approximately half of the consultations included a statement of a nutrition-related problem (52.2%; n=47), and the provision of nutrition advice that focused on a nutrient (45.6%; n=41) or food group (52.2%; n=47). Consultations with male GPs, as well as GPs with more than 25 years of experience, were associated with an increased number of nutrition care practices per consultation. DISCUSSION: The GPs performed nutrition care practices in varying frequencies. Further research is required to identify the most effective GP nutrition care practices to improve the nutrition behaviour of patients.